Utilisation of Bamboo As Reinforcement Material in Concrete - Mohd Noh, Hamidun; Ahmad Sukri, Nurul Hazwani; Idris, Nur’ain; Kasim, Narimah; Zainal, Rozlin; Shareh Musa, Sharifah Meryam (Research in Management of Technology and Business, 2021)
The use of reinforced concrete is not a new feature in the construction industry in Malaysia. Nowadays, the problem of overuse of steel in the industry, cracks and low strength of concrete had been issued especially in the low cost residential area. On the other hand, bamboo is a natural resources which have a big population and potential to be used in construction due to the strength, durability and ability to replace steel in concrete. So, bamboo culm will be used as reinforcement material in concrete to improve the problems. The research objective of this study are to compare the compressive strength of the bamboo with various diameters and to compare the structural strength of reinforced concrete with standard concrete. The experimental work consists of casting and testing the 100x100x100 mm of reinforced concrete with concrete cover/diameter (0.781, 0.971 and 1.224) in various diameters Ø29 , Ø34 andØ39) of bamboo culms. Then, the slump and compression test to determine workability and strength standard concrete and bamboo reinforced concrete were compared. The results of this study prove that bamboo culm are suitable to be used as reinforcement material and able to improve the strength and workability in reinforced concrete. Apart of reducing the usage of concrete and suitable to replace steel in reinforced concrete, this study is also to encourage the usage of natural renewable material as an alternative construction materials. It is also to educate society on the negative impact of carbon emission towards the environments and also to explore more on the potential of bamboo as an alternative material.